The Family, school, and the logic of academic failure - Campos Gomes, Hítala Maria (Guará Journal, 2025)
This work aims to demonstrate, through a project carried out at the José Áureo Monjardim Elementary School, that the learning difficulties present in the school today can also be seen as a symptom, which may have had their origins outside the school context. In these cases, psychoanalytic care becomes necessary and useful.
Keywords: School difficulties; Anxiety; Family; Psychoanalysis